Simple phenols from the distillation of Origanum vulgare assessed by UV spectrometry through auxochromes - Bravo Loor, Johnny Daniel (2021)
In order to determine the amount of phenols in an oily extract of Origanum vulgare leaves with an agile, accessible, economical and respectful procedure with the living environment, UV visible spectroscopy was used, creating a chromophore with iron III chloride. at 10,000 mg / L in 95% ethanol solution, a wave width of 330 nanometers and as a reference, a standard of 5-Isopropyl-2-methylphenol with a concentration of 997000 mg/L, dissolved successively (99 700 - 110 000 - 120 000 - 130000 - 140000 mg/L). The graphical representation of verification of the known quantities of phenols contained in the solutions and the product of the extraction by vapor drag of the leaves with respect to the absorbance, shows after the statistical analysis of variance by linear adjustment of the least squares, a linearity and precision in the procedure used, achieving concentrations between 120,000 and 140,000 mg/L of phenolic components such as carvacrol. It was possible to determine the amount of these polyphenols from Origanum vulgare, by establishing unsaturated groups and achieving optical densities in the UV spectrophotometer.